A Student Presence System and Its Development to the Internet of Things A Literature Review - Yanris, Gomal Juni (Internet of Things and Artificial Intelligence Journal, 2021)
Presence is one of the inherent aspects of the students. The presence system conducted in kindergarten Nurul Huda Kotapinang still uses a conventional system in the form of absent notes or books. This is considered less efficient because the data written by the teacher on the students still use the Presence book that is vulnerable to damage due to exposure to water and destructive things. Based on the background of the problems faced by teachers in kindergarten Nurul Huda Kotapinang, the authors designed the information system for students. This system is designed using Visual Basic .Net. In contrast, the programming language used is VBsrift and MySQL database. This system is designed and built to facilitate the delivery of information. The primary purpose of this system is to make it easier for teachers to attend to their students. It can be concluded Development Information System Presence can replace the confessional way previously used in kindergarten Nurul Huda Kotapinang into Student Presence Information Systems Based Visual Basic. As a development, this present system was modified in its programming language to produce a platform that is compatible with the Internet of Things Technology.